Association of component measurement variability and disease severity with variability of calculated mitral regurgitant fraction in dogs with myxomatous mitral valve disease - G. McAulay; D. Singleton; M. Rishniw (Journal of Veterinary Cardiology, 2026)

Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Recent Federal Nutrition Assistance Policy Shifts: Implications and Research Priorities - Rebecca Maida; Palak Gupta; Chelsea R. Singleton; Marissa McElrone; Julie D. Wright (Journal of Nutrition Education and Behavior, 2026)

Triple oxygen and hydrogen stable isotope composition of water in Murchison carbonaceous chondrite accessed by thermogravimetry-enabled laser spectroscopy - Erik J. Oerter; Alexandre Garenne; Miguel Cisneros; George D. Cody; Michael Singleton; Conel M. O’D. Alexander (Chemical Geology, 2025)

Diversity and physiology of abundant Rhodoferax species in global wastewater treatment systems - Jette F. Petersen; Laura C. Valk; Maarten D. Verhoeven; Marta A. Nierychlo; Caitlin M. Singleton; Morten K.D. Dueholm; Per H. Nielsen (Systematic and Applied Microbiology, 2025)

European Network for Optimization of Veterinary Antimicrobial Therapy (ENOVAT) guidelines for antimicrobial use in canine acute diarrhoea - L.R. Jessen; M. Werner; D. Singleton; C. Prior; F. Foroutan; A.A. Ferran; C. Arenas; C. R. Bjørnvad; E. Lavy; F. Allerton; K. Allensbach; L. Guardabassi; et al. (The Veterinary Journal, 2024)

Sodic-calcic alteration and transpressional shear along the Atacama fault system during IOCG mineralization, Copiapó, Chile - N. M. Seymour; J. S. Singleton; R. Gomila; G. Arancibia; J. Ridley; M. L. Gevedon; D. F. Stockli; S. M. Seman (Mineralium Deposita, 2024)
The Punta del Cobre district near Copiapó is a center of iron oxide-copper–gold (IOCG) mineralization spatially and temporally associated with regional sodic-calcic hydrothermal alteration, the Atacama fault system (AFS), and two phases of Early Cretaceous magmatism. Here, we investigate the spatiotemporal and geochemical relationships between magmatism, ductile deformation, and hydrothermal alteration along the ~ 200 to 300-m-thick steeply NW-dipping Sierra Chicharra shear zone, interpreted to be the major strand of the AFS. Mylonitic fabrics and oblique sinistral-reverse kinematic indicators together record coaxial flattening in a transpressional regime. Deformation on the AFS took place before, during, and after intrusion of the synkinematic Sierra Chicharra quartz diorite of the Coastal Cordillera arc at ~ 122 Ma and terminated before intrusion of the unstrained ~ 114 Ma Sierra Atacama diorite of the Copiapó batholith. Geochemical data show that the Copiapó batholith was more mafic and more K-rich than the calc-alkaline Coastal Cordillera arc. This time period thus overlaps IOCG mineralization in the Punta del Cobre district (~ 120 to 110 Ma). Multiple phases of sodic-calcic alteration in and around the AFS shear zone are recognized. Textures of altered rock in the shear zone show both synkinematic assemblages and post-kinematic hydrothermal oligoclase. A ~ 775-m-long andradite vein that cuts the shear zone formed broadly at the end of magmatism in the district (~ 95 Ma). Oxygen isotope ratios from the vein indicate that hydrothermal fluids were likely magmatically derived. Together, this work shows the AFS-related shear zone and nearby IOCG mineralization developed in a regional transpressional regime produced by SE-directed oblique convergence across a NE-striking shear zone. IOCG-related magmatic-hydrothermal fluids exploited this transcrustal shear zone to produce multiple episodes of regional sodic-calcic alteration formed from fluids exsolved from magmas or driven by the heat of the Coastal Cordillera arc and Copiapó batholith.

Efficacy of antimicrobial and nutraceutical treatment for canine acute diarrhoea: A systematic review and meta-analysis for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - K. Scahill; L.R. Jessen; C. Prior; D. Singleton; F. Foroutan; A.A. Ferran; C. Arenas; C.R. Bjørnvad; E. Lavy; F. Allerton; J.S. Weese; K. Allenspach; et al. (The Veterinary Journal, 2024)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Using the Exploration, Preparation, Implementation, and Sustainment (EPIS) Framework to Advance the Science and Practice of Healthy Food Retail - Bailey Houghtaling; Sarah Misyak; Elena Serrano; Rachael D. Dombrowski; Denise Holston; Chelsea R. Singleton; Samantha M. Harden (Journal of Nutrition Education and Behavior, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The density of odontocete integument depends on blubber lipid composition and temperature - Gina L. Lonati; Emily M. Singleton; Caitlin E. Phelps; Heather N. Koopman; D. Ann Pabst (Marine Mammal Science, 2019)
Cetacean integument serves many functional roles, including contribution to whole body buoyancy. The blubber of the integument of different cetacean species contains varying concentrations of triacylglycerols (TAG) and wax esters (WE); generally, these lipid classes have different densities. Integument can also experience a wide range of temperatures during a dive, so its density may change with depth. The goals of this study were to measure integument density and isolated blubber lipid density in three deep‐diving odontocete species ( n = 3–4)—short‐finned pilot whales ( Globicephala macrorhynchus ), pygmy sperm whales ( Kogia breviceps ), and Gervais' beaked whales ( Mesoplodon europeaus )—at different temperatures (6°C–35°C), and to relate these densities to lipid content and composition. Kogia and Mesoplodon integument and isolated lipids had high WE content (78.7–99.5 wt%) and were less dense (by 1.7%–9.3%) than those of Globicephala , which were composed predominately of TAG. Generally, densities increased as temperature decreased. Changes in integument densities mirrored those of isolated lipid densities, suggesting that blubber lipids are largely responsible for the buoyant properties of cetacean integument. These data demonstrate that the contribution of the integument to whole body density depends on lipid class and temperature, and therefore may provide useful, species‐specific correction factors for diving energetics models.

Lipid composition and thermal properties of the blubber of Gervais’ beaked whale ( Mesoplodon europaeus ) across ontogeny - Emily M. Singleton; William A. McLellan; Heather N. Koopman; Antje Pokorny; Frederick S. Scharf; D. Ann Pabst (Marine Mammal Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Mouse divalent metal transporter 1 is a copper transporter in HEK293 cells - Miguel Arredondo; María José Mendiburo; Sebastián Flores; Steven T. Singleton; Michael D. Garrick (BioMetals, 2014)

Connectivity Planning to Address Climate Change - TRISTAN A. NUÑEZ; JOSHUA J. LAWLER; BRAD H. MCRAE; D. JOHN PIERCE; MEADE B. KROSBY; DARREN M. KAVANAGH; PETER H. SINGLETON; JOSHUA J. TEWKSBURY (Conservation Biology, 2013)
As the climate changes, human land use may impede species from tracking areas with suitable climates. Maintaining connectivity between areas of different temperatures could allow organisms to move along temperature gradients and allow species to continue to occupy the same temperature space as the climate warms. We used a coarse‐filter approach to identify broad corridors for movement between areas where human influence is low while simultaneously routing the corridors along present‐day spatial gradients of temperature. We modified a cost–distance algorithm to model these corridors and tested the model with data on current land‐use and climate patterns in the Pacific Northwest of the United States. The resulting maps identified a network of patches and corridors across which species may move as climates change. The corridors are likely to be robust to uncertainty in the magnitude and direction of future climate change because they are derived from gradients and land‐use patterns. The assumptions we applied in our model simplified the stability of temperature gradients and species responses to climate change and land use, but the model is flexible enough to be tailored to specific regions by incorporating other climate variables or movement costs. When used at appropriate resolutions, our approach may be of value to local, regional, and continental conservation initiatives seeking to promote species movements in a changing climate. Planificación de Conectividad para Atender el Cambio Climático

Long-term simulation of in situ biostimulation of polycyclic aromatic hydrocarbon-contaminated soil - Stephen D. Richardson; Maiysha D. Jones; David R. Singleton; Michael D. Aitken (Biodegradation, 2012)

Pyrosequence analysis of bacterial communities in aerobic bioreactors treating polycyclic aromatic hydrocarbon-contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2011)

Stable‐isotope probing of the polycyclic aromatic hydrocarbon‐degrading bacterial guild in a contaminated soil - Maiysha D. Jones; Douglas W. Crandell; David R. Singleton; Michael D. Aitken (Environmental Microbiology, 2011)
Summary The bacteria responsible for the degradation of naphthalene, phenanthrene, pyrene, fluoranthene or benz[ a ]anthracene in a polycyclic aromatic hydrocarbon (PAH)‐contaminated soil were investigated by DNA‐based stable‐isotope probing (SIP). Clone libraries of 16S rRNA genes were generated from the 13 C‐enriched (‘heavy’) DNA recovered from each SIP experiment, and quantitative PCR primers targeting the 16S rRNA gene were developed to measure the abundances of many of the SIP‐identified sequences. Clone libraries from the SIP experiments with naphthalene, phenanthrene and fluoranthene primarily contained sequences related to bacteria previously associated with the degradation of those compounds. However, Pigmentiphaga ‐related sequences were newly associated with naphthalene and phenanthrene degradation, and sequences from a group of uncultivated γ‐ Proteobacteria known as Pyrene Group 2 were newly associated with fluoranthene and benz[ a ]anthracene degradation. Pyrene Group 2‐related sequences were the only sequences recovered from the clone library generated from SIP with pyrene, and they were 82% of the sequences recovered from the clone library generated from SIP with benz[ a ]anthracene. In time‐course experiments with each substrate in unlabelled form, the abundance of each of the measured groups increased in response to the corresponding substrate. These results provide a comprehensive description of the microbial ecology of a PAH‐contaminated soil as it relates to the biodegradation of PAHs from two to four rings, and they underscore that bacteria in Pyrene Group 2 are well‐suited for the degradation of four‐ring PAHs.

Effects of enrichment with phthalate on polycyclic aromatic hydrocarbon biodegradation in contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2008)

Identification and quantification of uncultivated Proteobacteria associated with pyrene degradation in a bioreactor treating PAH‐contaminated soil - David R. Singleton; Ramiah Sangaiah; Avram Gold; Louise M. Ball; Michael D. Aitken (Environmental Microbiology, 2006)
Summary Uncultivated bacteria associated with the degradation of pyrene in a bioreactor treating soil contaminated with polycyclic aromatic hydrocarbons (PAH) were identified by DNA‐based stable‐isotope probing (SIP) and quantified by real‐time quantitative PCR. Most of the 16S rRNA gene sequences recovered from 13 C‐enriched DNA fractions clustered phylogenetically within three separate groups of β‐ and γ‐Proteobacteria unassociated with described genera and were designated ‘Pyrene Groups 1, 2 and 3’. One recovered sequence was associated with the Sphingomonas genus. Pyrene Groups 1 and 3 were present in very low numbers in the bioreactor but represented 75% and 7%, respectively, of the sequences recovered from 16S rRNA gene clone libraries constructed from 13 C‐enriched DNA. In a parallel time‐course incubation with unlabelled pyrene, there was between a 2‐ and 4‐order‐of‐magnitude increase in the abundance of 16S rRNA genes from Pyrene groups 1 and 3 and from targeted Sphingomonas spp. over a 10 day incubation. Sequences from Pyrene Group 2 were 11% of the SIP clone libraries but accounted for 14% of the total bacterial 16S rRNA genes in the bioreactor community. However, the abundance of this group did not increase significantly in response to pyrene disappearance. These data indicate that the primary pyrene degraders in the bioreactor were uncultivated, low‐abundance β‐ and γ‐Proteobacteria not previously associated with pyrene degradation.

The major features of an infestation by the invasive weed legume gorse (Ulex europaeus) on volcanic soils in Hawaii - J. K. Leary; N. V. Hue; P. W. Singleton; D. Borthakur (Biology and Fertility of Soils, 2006)

Sodium Application Enhances DDT Transformation in a Long-Term Contaminated Soil - D. Kantachote; I. Singleton; R. Naidu; N. McClure; M. Megharaj (Water, Air, & Soil Pollution, 2004)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Anthropogenic radionuclides in tide-washed pastures bordering the Irish Sea coast of England and Wales - A. L. Sanchez; A. D. Horrill; B. J. Howard; D. Singleton; K. Mondon (Water, Air, & Soil Pollution, 1998)

Similarities in the behaviour of Chernobyl derived Ru-103, Ru-106 and Cs-137 in two freshwater lakes - J. Hilton; W. Davison; J. Hamilton-Taylor; M. Kelly; F. R. Livens; E. Rigg; D. L. Singleton (Aquatic Sciences, 1994)